Social enterprises and their ecosystems in Europe (Publications Office of the European Union, 2016)
The transition to a market economy stimulated the emergence of plurality within civil society initiatives that had been either dissolved or had become part of the Communist state system, and opened new pathways for entrepreneurial initiatives. The 1990s witnessed the flourishing of a significant number of non-profit organisations, including the pioneering establishment of the first social enterprises, which emerged bottom-up in a variety of fields of general interest. Later on, when the Slovak Republic entered the European Union, the process of legal institutionalisation of social enterprises started to be discussed and has taken place in general through two distinct strategies. First, through the reform in social services, which followed the transformation of the public-sector-driven institutional care model into a community-based service system that allows for participation of non-state actors on the provision of a variety of social services. Second, through the introduction of a general legal framework, which is specifically designed to regulate enterprises integrating disadvantaged workers (WISEs).
10.2767/789970
Keywords: Amtsdruckschrift; Graue Literatur; Sozialwirtschaft; Slowakei; social policy; social economy; social impact; European undertaking; financial aid; entrepreneurship; investment; cartography; Slovakia; report